Prepare, deliver, shepherd : using evaluation to understand the impact of ethos in preaching - Wade, William H., Jr., 1968- (2013)
1 online resource (1 PDF (ix, 159 leaves)); Typescript; Includes abstract; Thesis (D. Min.)--Covenant Theological Seminary, 2013; Bibliography: leaves 154-159